2013
DOI: 10.1089/ten.tea.2012.0358
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Re-Differentiation of Passaged Rat Chondrocytes Using a Naturally Obtained Extracellular Matrix Microenvironment

Abstract: Dedifferentiated human chondrocytes severely limit successful hyaline cartilage repair in clinical practice. The primary interest of this study is to evaluate the naturally obtained cell-derived matrix (CDM) as a physical microenvironment for chondrocyte re-differentiation. Once different cell types were cultured for 6 days and decellularized using detergents and enzymes, the fibroblast-derived matrix (FDM), preosteoblast-derived matrix (PDM), and chondrocyte-derived matrix (CHDM) were obtained. From scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…Alternately, differential integrin activation (via a4b1, a5b1, or avb3) by Fn domains may contribute to cell survival, differentiation, or matrix remodeling. [45][46][47][48][49][50] Thus, the observations demonstrated within may suggest a mechanism wherein Fn or its fragments function in an autocrine manner to promote the enhanced GAG content and E Y observed in the -COOH surface functionalized group. Further work is required to demonstrate whether altered Fn1 expression in -COOH surface functionalized groups concomitantly influences cognate integrin expression and whether this provides an instructive signal toward chondrogenic phenotype and matrix production.…”
Section: Discussionmentioning
confidence: 79%
“…Alternately, differential integrin activation (via a4b1, a5b1, or avb3) by Fn domains may contribute to cell survival, differentiation, or matrix remodeling. [45][46][47][48][49][50] Thus, the observations demonstrated within may suggest a mechanism wherein Fn or its fragments function in an autocrine manner to promote the enhanced GAG content and E Y observed in the -COOH surface functionalized group. Further work is required to demonstrate whether altered Fn1 expression in -COOH surface functionalized groups concomitantly influences cognate integrin expression and whether this provides an instructive signal toward chondrogenic phenotype and matrix production.…”
Section: Discussionmentioning
confidence: 79%
“…To evaluate the effect of different CDMs on chondrocyte dedifferentiation, rat primary chondrocytes were cultured on TCPS for 4 passages to induce dedifferentiation, marked by loss of collagen type II and aggrecan expression. When transferred to the CDMs and cultured for an additional 2 weeks, the passaged chondrocytes exhibited signs of redifferentiation, including increased GAG and collagen type II deposition and reduced collagen type I gene expression, although the gene expression levels of collagen type II and aggrecan were similar in all cultures 57 . Pellet cultures of dedifferentiated chondrocytes expanded on CDM for 2 passages also contained more GAGs, stronger peripheral staining of collagen type II and were larger in size compared to pellets formed from TCPS-expanded chondrocytes 57 .…”
Section: Cell-derived Matrices As Models Of Stem Cell Niches and Ex Vmentioning
confidence: 99%
“…A common limitation in expanding sensitive primary cells ex vivo is loss of the native phenotype, characterized by loss of function, senescence, dedifferentiation and/or spontaneous differentiation 57-61 . One approach to mitigate culture-induced phenotypic changes is to recapitulate the tissue-specific microenvironment, in addition to the use of soluble factors.…”
Section: Cell-derived Matrices As Models Of Stem Cell Niches and Ex Vmentioning
confidence: 99%
“…[4][5][6] These ECM materials can be obtained from cell-derived matrices secreted during in vitro culture or from native tissue, 4,[7][8][9][10][11] and they have either been decellularized to remove cellular components and nucleic acids or they have been devitalized to kill but not necessarily remove cells within the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…We and other groups have already established that cartilage matrix has chondroinductive potential, 7,[13][14][15][16][17] and we recently were the first to compare the chondroinductive potential of two different types of cartilage matrix in pellet culture: devitalized cartilage (DVC), where the matrix was exposed to a freeze/thaw process to devitalize the living chondrocytes within the matrix, and decellularized cartilage (DCC), in which the cells were not only devitalized but also removed from the matrix entirely. 17 In the pellet culture study, we observed that rat bone marrow stem cells (rBMSCs) exposed to DCC outperformed those cells exposed to DVC or transforming growth factorb 3 (TGF-b 3 ) in chondroinductivity.…”
Section: Introductionmentioning
confidence: 99%